2014
DOI: 10.1590/1415-52732014000200004
|View full text |Cite
|
Sign up to set email alerts
|

Association between sociodemographics factors and dietary patterns during pregnancy

Abstract: OBJECTIVE: To investigate the association between socio-demographic factors and dietary patterns in pregnancy. METHODS: Cross-sectional study with baseline data from a cohort of 421 postpartum women aged 18 and 45 years resident in Rio de Janeiro, Brazil. Dietary intake was evaluated with a validated food frequency questionnaire at 15 days following delivery, having as time frame the second and third pregnancy trimesters. Dietary patterns were identified using factor analysis for principal components analysis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
1
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 34 publications
0
12
1
3
Order By: Relevance
“…Although our study has identified three dietary patterns before the pregnancy period, they were similar to other studies that derived patterns during pregnancy. 44,45 Our study has a higher total variance explained by patterns when compared with previous studies, which reported 31.3% and 23.5% of variance explained, respectively. These data explain the percentage of variability of diet in a specific population 21 ; that is, the common-Brazilian pattern was the most consumed in our sample because it had a higher percentage of variance explained, and all patterns together represent 36.2% of dietary variability of our population.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…Although our study has identified three dietary patterns before the pregnancy period, they were similar to other studies that derived patterns during pregnancy. 44,45 Our study has a higher total variance explained by patterns when compared with previous studies, which reported 31.3% and 23.5% of variance explained, respectively. These data explain the percentage of variability of diet in a specific population 21 ; that is, the common-Brazilian pattern was the most consumed in our sample because it had a higher percentage of variance explained, and all patterns together represent 36.2% of dietary variability of our population.…”
Section: Discussioncontrasting
confidence: 59%
“…These patterns are similar to a mix of our common-Brazilian and healthy patterns. Castro and colleagues 45 identified two dietary patterns in Brazilian pregnant women: "healthy," characterized by fruits, green vegetables, vegetables, fish, roots/corn/and potato, milk/dairy, and herbal tea, and negative loadings for alcohol and coffee, which is extremely similar to our pattern also called healthy. The "mixed" pattern was composed of rice, beans, flour/pasta, breads, cake/cookies, soda/juice, sugar/sweets, fatty foods, meats, chicken, and eggs, and had food groups contained in the three dietary patterns identified in our study.…”
Section: Discussionmentioning
confidence: 53%
“…Since the early 1990s, principal component analysis has been used to identify dietary patterns during pregnancy (9)(10)(11) . This method allows for diet to be described as a whole, and it can be used to assess the role of social and economic factors in the likelihood of adherence to a certain dietary pattern.…”
mentioning
confidence: 99%
“…Similarly, principal component analysis provides additional information for exploring the relationship between nutrition and health (12)(13)(14) . There are still gaps regarding the impact of various socio-economic and demographic factors on adequate dietary intake during pregnancy (9,15) . In Brazil, a study of 421 pregnant women, conducted by Castro et al (9) , indicated that schooling and family income were positively associated with a 'healthy' dietary pattern.…”
mentioning
confidence: 99%
“…O padrão alimentar "saudável" associou-se positivamente com a renda e a escolaridade, e negativamente com a paridade e a etnia. O padrão "misto" associou-se positivamente com a etnia e o estado marital, e negativamente com a renda e a escolaridade (CASTRO et al, 2014).…”
Section: Padrão De Consumo Alimentar De Gestantesunclassified